2013
DOI: 10.1097/mpg.0b013e31827913f9
|View full text |Cite
|
Sign up to set email alerts
|

Human Leukocyte Antigen DQ2.2 and Celiac Disease

Abstract: Patients with celiac disease (CD) lacking both human leukocyte antigen (HLA)-DQ2.5 in cis (DQA1*05:01, DQB1*02:01) or trans (DQA1*05:05, DQB1*02:02) configuration and HLA-DQ8 (DQA1*03:01, DQB1*03:02) are considered to be rare. Therefore, absence of these genotypes is commonly used to exclude the diagnosis of CD. To investigate whether this approach is justified, the HLA-distribution in 155 children with CD was studied. A total of 139 (89.7%) patients carried HLA-DQ2.5. Of the remaining patients, 7 (4.5%) carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 19 publications
3
30
0
7
Order By: Relevance
“…Previous studies already showed that a great proportion of DQ2.5 and DQ8 negative CD patients were positives for the DQ2.2 variant (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) concluding that DQ2.2 should be considered as a risk variant for celiac disease. Other studies also gave details on the probable molecular role of the heterodimer coded by this variants (18,19) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies already showed that a great proportion of DQ2.5 and DQ8 negative CD patients were positives for the DQ2.2 variant (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) concluding that DQ2.2 should be considered as a risk variant for celiac disease. Other studies also gave details on the probable molecular role of the heterodimer coded by this variants (18,19) .…”
Section: Discussionmentioning
confidence: 99%
“…However, due to their heterogeneous distribution in different populations around the world, genotypes' prevalence must be first characterized for the local population to be able to compare it to at-risk subjects. The inclusion of HLA-DQ2.2 as a predisposing variant for celiac disease remains under discussion with it being significant for some but not all studied populations (6)(7)(8)(9)(10)(11)(12)(13) . Although about 30%-40% of the general population carry HLA-DQ2 and/or DQ8 without developing CD, these alleles are absent in less than 0.5% of CD patients (14) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussions are still held among the choice of forms of screening with the best combination, including good specificity, sensitivity and lower cost of a shorter period of time from receipt of materials, through processing to delivery of the actual outcome. Elsewhere, there is a support for the implementation of some special genetic test [11]. Other authors recommend that each endoscopy biopsy sampling implement should contain several samples of small intestine with special needs in functional dyspepsia, or even regardless of the cause of examination [9,15].…”
Section: Tasks and Four-step Individual Managementmentioning
confidence: 99%